2019
DOI: 10.3390/molecules24101906
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Okra (Abelmoschus esculentus (L.) Moench) Improves Antioxidant Capacity via PI3K/AKT Pathways and Nrf2 Translocation in a Type 2 Diabetes Model

Abstract: Polysaccharide extracted from okra (Abelmoschus esculentus (L.) Moench), a traditional functional food, is a biologically active substance reported to possess hypoglycemic and anti-oxidative qualities. However, it is unknown which polysaccharides play a role and have the potential mechanism. This present study is to assess the possible impacts of a novel polysaccharide isolated from okra (OP) on mice fed with a high-fat diet (HFD) combined with an intraperitoneal injection (i.p.) of 100 mg/kg streptozotocin (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 34 publications
5
79
0
2
Order By: Relevance
“…[28] Specifically, activation of PI3K/ Akt signaling pathway further stimulated conveyance of blood glucose into the cytoplasm of muscle cells via GLUT4, then, glucose converted to glycogen. [25] Furthermore, relative expression levels of PI3K and Akt at mRNA level were shown in Figure 7, the current data demonstrated that the expression of PI3K and Akt in skeletal muscle of diabetic rats from DC group were markedly down-regulated compared with those of NC group (P < 0.05), reducing approximately by 45.54 % and 61.90 %, separately. Oral administration with metformin or HFP was certificated a remarkable extremely up-regulation in the expression of PI3K and Akt in skeletal muscle of diabetic rats compared to DC group (P < 0.05).…”
Section: Effects Of Hfp On Genes Expression Of Skeletal Muscle In Diasupporting
confidence: 59%
“…[28] Specifically, activation of PI3K/ Akt signaling pathway further stimulated conveyance of blood glucose into the cytoplasm of muscle cells via GLUT4, then, glucose converted to glycogen. [25] Furthermore, relative expression levels of PI3K and Akt at mRNA level were shown in Figure 7, the current data demonstrated that the expression of PI3K and Akt in skeletal muscle of diabetic rats from DC group were markedly down-regulated compared with those of NC group (P < 0.05), reducing approximately by 45.54 % and 61.90 %, separately. Oral administration with metformin or HFP was certificated a remarkable extremely up-regulation in the expression of PI3K and Akt in skeletal muscle of diabetic rats compared to DC group (P < 0.05).…”
Section: Effects Of Hfp On Genes Expression Of Skeletal Muscle In Diasupporting
confidence: 59%
“…HbA1c is a valuable indicator for the diagnosis and management of hyperglycemia in diabetes and levels lower than 7% indicate good glycemic control [65]. Previous work from our lab [15] as well as others [66,67] have shown hyperglycemia, elevated HbA1c% and altered insulin secretion, and sensitivity in HFD/STZ-induced rodents. In addition, the values of HOMA-IR suggested the development of IR in HFD/STZ-induced rats.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, these polysaccharides improved SOD, CAT, and GSH-Px activities in liver and kidney tissue of diabetic mice. Tea polysaccharides increased the expressions of PI3K/AKT p-AKT and GLUT4 signaling pathway [27,88,152]. All these above findings proved that administration of polysaccharides remarkably inhibited the expression of GSK-3 β and elevated expressions of the insulin receptor, IRS1, PI3K, and AKT in type 2 diabetic animal models.…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 97%
“…Sea cucumber polysaccharide (MW: 21.53 kDa) purified from Acaudina Molpadioides (MW: 20.53 kDa,) and pumpkin polysaccharides (MW: 749.3, 727.0, and 607.6 kDa) and sulfated rhamnose polysaccharides (MW: 4.57 kDa) from Enteromorpha prolifera increased insulin-stimulated glucose uptake, GLUT4 translocation, and Akt/ERK activation in TNF-α-induced insulin-resistant 3T3-L1 adipocytes. This finding strongly suggested that polysaccharide enhanced glucose uptake by activating the PI3K/Akt pathway and MAPK–ERK pathway [90,150,151,152]. Another in vitro study connected with active polysaccharides on LPS-induced RAW 264.7 cells; polysaccharides derived from Agaricus blazei Murill decreased the expression of JNK, ERK, and p38 [132,153,154].…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 99%